Nanotechnology and Scientific Communication : Ways of Talking about Emerging Technologies and Their Impact on Society (2004-2008) - Bassett, Deborah R. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This study examines findings from a 4-year-long ethnography of communication among a research university's community of scientists and engineers working in nanoscience and nanotechnology. It includes analysis of 20 in-depth interviews with scientists and engineers from 18 different disciplines self-identified as working in nanoscale science and engineering. Using multiple methods of inquiry, including fieldwork, interviews, and textual analysis, elements of a shared speech code are presented, each of which indicate culturally distinctive understandings of psychology, sociology and rhetoric. In particular, the interview data addresses questions such as "What kind of person is a scientist?" "What is the role of science in society?" and "What is the role of communication in science?" This book will appeal to readers interested in science and society, scientific communication, and ethnography of communication.
Keywords: Social sciences.; Engineering ethics.; Computers and civilization.; Nanotechnology.; Sociology.; elektronické knihy; electronic books